Haemonchosis in Small Ruminants Under Traditional Husbandry Systems in Apac District, Northern Uganda - Charles Dickens Opeto; Harriet Angwech; Acaye Ongwech; Benard Abola; Steven Odongo; Geoffrey M. Malinga (Journal of Parasitology Research)
Haemonchus contortus is one of the most common and fatal pathogenic gastrointestinal nematodes of small ruminants causing significant economic losses, particularly in low-income countries. A cross-sectional study was carried out in randomly selected small ruminants kept under traditional husbandry systems in the Apac district (now split into Apac and Kwania districts) in northern Uganda to assess the prevalence, intensity, and associated risk factors of H. contortus infection from May 2018 to January 2019. Faecal samples were collected from a total of 768 randomly selected small ruminants (384 sheep and 384 goats) and examined for parasites using the floatation method and coproculture. The overall prevalence of H. contortus in small ruminants was 73.3% (563/768) by faecal egg count and 70.6% (542/768) by coproculture. The mean number of eggs per gram of faeces in small ruminants was 2046±107 and differed significantly across the host animals ranging from 1729±120 (mean±SE) in goats to 2364±176 in sheep. Significant predictors of infection were the origin of study animals, animal species, breed of animal, age of study animal, faecal consistency, lactation, multispecies grazing, grazing method, and anthelmintic use. The findings of our study provide information on the current status of H. contortus infections in goats and sheep under traditional husbandry systems in Uganda which are critical in designing effective control strategies for the disease.